Training and Guidance on the Preparation of Islamic Value Based Lesson Plans and Writing Classroom Action Research for Mathematics Teachers at Lhokseumawe Vocational High School - Setiawan, Setiawan; Yusnaini, Yusnaini (Electronic Journal of Education, Social Economics and Technology, 2024)
Activities carried out in community service for Lhokseumawe City Vocational School mathematics teachers are Classroom Action Research (CAR) writing activities and designing lesson plans based on Dinul Islam. The aim of this activity is for Lhokseumawe City Vocational School mathematics teachers to be able to create CAR and design lesson plans based on Dinul Islam on an ongoing basis in order to improve teacher careers. The form of this activity is to carry out training and mentoring for 4 days from 26 to 29 April 2021 with a total time of 32 JP with an allocation of 2 days of training and mentoring for CAR writing and 2 days for designing Dinul Islam-based lesson plans. This is then continued with assistance in the form of guidance in writing CAR and lesson plans based on Dinul Islam from May to June 2021. The work system carried out by teachers is group in nature and they work together in determining the CAR title and writing CAR. Meanwhile, the work system in designing Dinul Islam-based RPPs is individual. The results obtained resulted in 10 CAR titles with continuous writing, while Dinul Islam-based lesson plans were printed and 26 lesson plans were collected from 30 participants.